If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -9x = 131 Solving 23 + -9x = 131 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -9x = 131 + -23 Combine like terms: 23 + -23 = 0 0 + -9x = 131 + -23 -9x = 131 + -23 Combine like terms: 131 + -23 = 108 -9x = 108 Divide each side by '-9'. x = -12 Simplifying x = -12
| a^4-9a^2+29=0 | | c+5d-12c= | | 2(lnx+1)=0 | | 0.10x+0.05(2-x)=0.10(5) | | 0.10x+0.05(2-x)=0 | | k^2-20k+64=0 | | 27x^6-27x^5+45x^3/-9x^3 | | 16-5(3t-4)=88(-2t+11) | | -8y=-33 | | 8y=-33 | | 5/12k=1/15-3/14 | | 85x-16=0 | | 6x-1=2x+1 | | cos(3x)-sin(2x)=0 | | 22-x=5+6x+9 | | 0=x^2-10x+28 | | 13y=1/15-3/14 | | -9x^2+4x-16=0 | | 3n^3+9n^2-84n=0 | | 4.90=0.05x+1.90 | | 3x-6=25x+18 | | 4(w-2)=0.6 | | 88-40=13/4(h-5) | | (2x-6)+(x+7)= | | 25-n^2=0 | | 23x-5=0 | | 12x-4x^2-9=0 | | 12q^2-17q+5=0 | | 6(x+2)=2(x+10) | | 25b+11-6b^2=0 | | 8x/6=72/54 | | 0.1q-0.2(3q+4)=-0.3(5q+3) |